Patient-Reported Outcome Instruments in Spine Surgery. Issue 5 (March 2016) - Guzman, Javier Z.; Cutler, Holt S.; Connolly, James; Skovrlj, Branko; Mroz, Thomas E.; Riew, K. Daniel; Cho, Samuel K.
Abstract : Study Design: A critical review of the current literature. Objective: The purpose of this study was to determine frequency, trends, and methods of utilization of spine-related PROIs over the last 10 years. Summary of Background Data: Patient-reported outcome instruments (PROIs) have become the gold standard to assess the efficacy of various medical and surgical treatments. Currently, however, there is an expansive range of PROIs without a clear consensus or guideline addressing which PROIs should be used for a particular diagnosis or surgical intervention. Methods: A PubMed search was conducted from 2004 to 2013 of 5 orthopedic journals ( The Journal of Bone and Joint Surgery, The Bone and Joint Journal, The Spine Journal, The European Spine Journal, and Spine ) that publish spine articles, chosen on the basis of readership and impact factor. Journal abstracts were inspected for spine surgery and inclusion of at least 1 PROI. All articles containing PROIs and investigating a surgical intervention with a level of evidence (LOE) 1 to 4 were included for analysis. Article title, LOE, journal, and chosen PROI were recorded for selected articles. Results: Out of 19, 736 articles published in our selected time frame, 1, 079 utilized PROIs. Most studies were LOE 4 (32.7%). Nearly half (48.9%) of all articles addressed degenerative thoracolumbar conditions. In total, there were 206 unique PROIs in the studies chosen for inclusion. The top 6 instruments utilized were the (1) visual analog scale, (2) Oswestry disability index, (3) Short Form-36, (4) Japanese Orthopaedic Association Outcome Questionnaire, (5) Neck Disability Index, and (6) Scoliosis Research Society-22. Conclusion: The breadth of PROIs in spine surgery is extensive. Although there are preferred patient-reported outcome measures, a consensus or guideline addressing which instruments should be used for a particular diagnosis or procedure may be warranted. Level of Evidence: 4